U.S. Postal Airmail Routing Optimization - Li, Yihua; Miao, Qing; Wang, Bruce X. (Transportation research record, 2013)
An airmail routing problem at the United States Postal Service (USPS) is studied in this paper. Each day, millions of airmails of different priorities are collected and shipped between local USPS mail processing and distribution centers (P&DCs) by commercial air carriers. The carriers provide flight capacities and services according to contracts. Each available flight has a finite, maximum capacity for the airmails. In addition, the shipping between P&DCs incurs a cost that is determined by the type of mail, the volume, and the shipping distance. The research objective is to decide airmail allocation onto flights subject to the agreed-on air capacity to minimize system shipping costs while maintaining service quality. An integrated mathematical model is developed to design air routes and to allocate airmails optimally to routes for an improvement on the practice of isolated scheduling at each P&DC. A column generation method is proposed for the model. A numerical test is conducted with operational data. The test not only shows a significant increase in the total volume that can be shipped but also indicates better service in terms of on-time and early deliveries.